Determination of side effects and medication adherence in major depression patients utilized antidepressants - OKUYAN, BETÜL; SANCAR, MESUT (MARMARA UNIV, FAC PHARMACY, 2016)
The aim of the study is to determine side effects, and medication adherence in patients who were diagnosed with major depression utilized antidepressants. This study was conducted in outpatient psychiatry clinic between February 2013 and May 2013. 'Toronto Side Effects Scale' and 4-item Morisky-Green-Levine Medication Adherence Scale were evaluated. Fifty-six major depression patients (mean of age: 40.82 +/- 14.28 years old; male/female: 13/43) were included in this study. Patients were treated with escitalopram (46.4%), sertraline (26.8%), venlafaxine (10.7%), citalopram (8.9%) and paroxetine (7.1%). The most common side effects that patients reported were drowsiness/daytime somnolence (57.1%), dry mouth (46.4%) and increased sleep (46.4%), increased appetite (37.5%) and malaise or fatigue (30.4%). The most severity side effects that patients experienced were drowsiness/daytime somnolence (25%), increased sleep (19.6%) and decreased libido (14.3%). Only fifteen (26.8%) patients were found high adherent to their medication. It was concluded that although the frequency and severity of side effects have been found high, the percentage of patients' medication adherence has been obtained low. Patient education and monitoring regarding side effects and medication adherence providing by pharmacists would be contributed to prevent possible drug induced problems in these patients besides the routine services they are taken from outpatient clinic.
Keywords: Depression; Side Effects; Patient adherence; PHARMACIST INTERVENTION; OUTCOMES; CARE; IMPACT